Antibacterial Effect of Diode Laser and Silver Nanoparticles against Biofilm Bacteria - Thamer Mutlag Jasim (Journal of Global Pharma Technology, 2018)
The present study has been undertaken to illustrate the antibacterial effect of diode laser and nanoparticle on isolated resistant biofilm bacteria. From the patient with urinary tract infection (UTI).Atotal of 90(56%) urine samples from patients with urinary tract infection (UTI) from Al Yarmuk hospital in Baghdad showed growth on culture. Proteus mirabilis was the most common pathogen accounting for 21(37.5), Staph aureus 20 (35.7), Klebsiella pneumonia 15(26.78). The biofilm bacteria exposed to diode laser after focal with alens of (15) cm after focal point for different time 0.5, 1, 1.5, 2, 2.5, 3 min. The synthesized nanoparticle was characterized by UV-spectroscopy. The antibacterial activity of synthesized silver nanoparticle was compared by agar well diffusion method. The effect of minimum inhibitory concentration (MIC) and sub (MIC) concentration of Ag NPs were determined by microtiter plate assay. The antibacterial effect of Ag NPs and diode laser has already been studied, Ag NPs, Laser group within our results, we found that that Ag NPs with lasers present low values in comparison With Ag NPs alone. The MIC value were higher these difference could due to divergence found in the cellular wall of each kind of bacteria. The synthesized silver nanoparticle and diode laser have shown good antibacterial efficacy as compared to laser alone and may prove to be better antibacterial agent against biofilm bacteria. The result showed the biofilm bacteria completely killed after exposure to diode laser for 3min with nanoparticles. In this study, synthesized Ag NPs have the efficient antibacterial activity against biofilm bacteria. Ag NPs have an important function in the field of nanotechnology. The results of this work revealed the potential of the synthesized Ag NPs as safer bactericidal agent against biofilm bacteria. The laser light enhances the antibacterial activity of silver nanoparticles by at least one fold. It conclude that the Ag Nps combined with laser exposure be used as local effective antibacterial approach inhibit the bacteria isolated from Urinary tract infection. The result stated that Ag NPs synthesized were nontoxic and good antibacterial agent against biofilm bacteria. These result that Ag NPS could be used as an adjuvant for the treatment of UTI infection disease.Keywords: Biofilm, Diode laser, Nanoparticle, antibacterial.